Abu zeaar al-Ghafari and advocacy to address poverty - obeida, sam (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study dealt with a part of the life of the Companion Abu zeaar al-Ghafari and his approach to the most important and mentioned in terms of his coming to the Prophet and his entry into Islam and the call of Muhammadiyah, in addition to the study of this bold ideas and his continuing calls to adhere to the book of God and the year of his prophet, The study focused on the call by Abu zeaar to distribute wealth to the poor and equality among them, as the researcher showed in this study the most important reasons for the process of exile to Abu Dhar and the way we exile to more than one place , In the end, the researcher said the most important words and conversations reported from Abu zeaar to show what research is well prepared for.